Optimasi Sistem Pembangkit Listrik Tenaga Hybrid di Pulau Enggano - Dyah Ayu Kartika Sari; Fransisco Danang Wijaya; Husni Rois Ali (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2022)
Enggano Island is one of the outermost regions using diesel power plants (Pembangkit Listrik Tenaga Diesel - PLTD) as their source of electrical energy. PLTD, which began its operations in 2017, consists of three units of generator machines capable of generating 730 kW of power, with a total of 1,050 customers and electricity needs of 1,097,883 kWh/year. Although power plants are readily available, in reality, the electricity problem is still a fundamental unresolved issue on the island. The average fuel consumption to operate a PLTD is 21 tons/month or Rp582,757,000.00 per month, assuming the fuel price is Rp9,800.00 per liter. The high operating expenses resulted in electricity only being supplied for sixteen hours per day. The utilization of PLTD also produces very high carbon dioxide (CO2) emissions. It is not in line with the government's commitment to transition to net zero emissions by 2060. The utilization of new renewable energy (Energi Baru dan Terbarukan - EBT), targeted at 23% by 2025, is still not optimal. The paper aims to discover Enggano Island's optimal hybrid power plant configuration in terms of technicality and economic feasibility. Economic feasibility is reviewed using the net present cost (NPC), and cost of economic (COE) approaches. In addition, sustainability analysis is also carried out from environmental aspects. From this study, the most optimal configuration based on the lowest system cost was configuration 2 of scenario 1, consisting of photovoltaic (PV) 1,005 kW, diesel of 250 kW, and 594 battery units. This configuration can produce electricity of 1,576,115 kWh/year with an NPC value of Rp31.7 billion rupiah and a COE value of Rp1,998.75 per kWh. This configuration also has good environmental sustainability because it has a renewable fraction value of 91%.